Longitudinal Morphological and Functional Assessment of RGC Neurodegeneration After Optic Nerve Crush in Mouse - Li, Liang; Huang, Haoliang; Fang, Fang; Liu, Liang; Sun, Yang; Hu, Yang (Frontiers in Cellular Neuroscience, 2020)
The mouse optic nerve crush (ONC) model has been widely used to study optic neuropathies and central nervous system (CNS) axon injury and repair. Previous histological studies of retinal ganglion cell (RGC) somata in retina and axons in ON demonstrate significant neurodegeneration after ONC, but longitudinal morphological and functional assessment of RGCs in living animals is lacking. It is essential to establish these assays to provide more clinically relevant information for early detection and monitoring the progression of CNS neurodegeneration. Here we present in vivo data gathered by scanning laser ophthalmoscopy (SLO), optical coherence tomography (OCT), and pattern electroretinogram (PERG) at different time points after ONC in mouse eyes and corresponding histological quantification of the RGC somata and axons. Not surprisingly, direct visualization of RGCs by SLO fundus imaging correlated best with histological quantification of RGC somata and axons. Unexpectedly, OCT did not detect obvious retinal thinning until late time points (14 and 28-days post ONC) and instead detected significant retinal swelling at early time points (1-5 days post ONC), indicating a characteristic initial retinal response to ON injury. PERG also demonstrated an early RGC functional deficit in response to ONC, before significant RGC death, suggesting that it is highly sensitive to ONC. However, the limited progression of PERG deficits diminished its usefulness as a reliable indicator of RGC degeneration.